Spatial Data Mining in Agriculture in Latin America - A Conceptual Approach - Gil-Torres, Andrés Felipe; Monroy-García, Aura Liliana; González-Sanabria, Juan Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Due to the increase in the use of GIS, it is necessary to know complementary techniques such as spatial data mining. This paper is a review of some of the existing techniques, as well as which of these provide greater benefits, revealing trends in their application in agriculture. Additionally, because in this area several variables are manipulated, tools are presented to facilitate the making decision process, by providing the result of evaluating the available data.